Playground for practising design thinking.: Training activities and toolkits for teaching problem framing. - Pei, Xue; Sgro, Leandro (Convergences - Journal of Research and Arts Education, 2025)
This study adopts the metaphor of a “Playground” to explore how to create effective learning environments and situated guides and tools that enable non-design students to learn and practice the early phases of the design process: design research and problem framing. Grounded in both theoretical frameworks and the authors’ practical experience in applying and teaching design thinking, the research introduces a structured yet adaptable visual toolkit aimed at supporting educators in facilitating design-based learning for students with non-design backgrounds. The toolkit was developed and refined through an iterative action research approach across three higher education courses. Emphasising empathy, ambiguity navigation, and creative exploration, it seeks to cultivate key designer mindsets and problem-framing capabilities. The findings present both practical toolkits, including the process and specific tools, and pedagogical insights for educators and researchers who apply design thinking to interdisciplinary educational contexts. This research contributes to the ongoing discourse on design pedagogy by examining the opportunities and challenges of transferring design thinking methodologies and practices across disciplines. It underscores the value of situated and experiential learning strategies in fostering a designerly approach to complex problem-framing in non-design domains.